"Every time that month comes, I remember": using cognitive interviews to adapt grief measures for use with bereaved adolescents in South Africa. Issue 2 (29th July 2016) - Taylor, Tory M; Thurman, Tonya R; Nogela, Lineo
Abstract : Objective: To assess standard grief measures through cognitive interviews with bereaved adolescents in Free State, South Africa, and make recommendations designed to improve the measurement of grief in this and similar populations. Methods: Twenty-one parentally bereaved adolescents participated in semi-structured cognitive interviews about the Core Bereavement Items (CBI) questionnaire, Grief Cognitions Questionnaire for Children (GCQ-C), or Intrusive Griefs Thoughts Scale (IGTS). Results: Interviewees offered valuable insights for improving grief measurement with this population (e.g., consensus that not thinking frequently about a deceased loved one was shameful, aversion to terms including "died"). Participants were better able to apply response options denoting specific frequencies (e.g., "once or twice a week") versus general ones (e.g., "a little bit of the time"). Questions intended to gauge grief commonly elicited responses reflecting the impact of loss on adolescents' basic survival instead of psychological wellbeing. Conclusions: The need for psychological support is high among orphans and vulnerable children. Tools for measuring psychological outcomes can provide evidence of programme effects and guide decision making about investment. Grief measures used with adolescents in South Africa should account for the issues raised by cognitive interviewees in the study, including question and response option complexity, linguistic preferences, and cultural norms.